Experimental determination of carbamate formation and amine protonation constants in 3-amino-1-propanol–CO2–H2O system and their temperature dependency. (June 2015) - Benamor, Abdelbaki; Al-Marri, Mohammed Jaber; Hawari, Alaa
Abstract: The equilibrium constant for the formation of carbamate in 3-amino-1-propanol–CO2 –H2 O system was evaluated at different CO2 loadings, different temperature values, and different amine protonation constant. The studied temperature varied from 298 to 328 K in an increment of 10 K and ionic strengths up to 1.5 M. The variation of the thermodynamic equilibrium constant with temperature was modeled according to the relationship of log K 1 = 1846.8/ T − 4.4152, while temperature dependency of amine protonation constant was correlated by log K 2 = 2786.5/ T + 0.5253.